Implementasi Program Beras Miskin (Raskin) Bagi Masyarakat Berpenghasilan Rendah Di Kelurahan Sawang Bendar Kecamatan Tahuna Kabupaten Kepulauaan Sangihe - Kongginawan, Gideon; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract :This research moved from initial findings that the implementation of the program in the VillageSawang Bendar Raskin indicated less effective, less targeted and not just the right amount. Thus, thisstudy aims to determine how the Raskin program implementation and obstacles that reported in theprocess of implementation of the Raskin program.To answer the research problem, then applied descriptive method kualitastif. Data collected byobservation, interview and documentation, kemudiaan 10 (ten) the informant set of elements of theDistrict government Tahuna many as four people, four persons from the village government Sawangbendar and 2 persons from the RTS-PM. Interactive techniques used to analyze the data.Results of the study showed that: (1) Rice program impelemntasi Poor (Raskin) in Sub Sawangsubdistrict Bendar Tahuna, in general has done well and is quite effective, but there are two dimensions,namely resources and implementing organizational structure is not optimal achievable. (2) There areseveral factors inhibiting or obstacles in the implementation of Raskin, particularly in Sub SawangBendar, namely: (a). Weather constraints in the distribution of Raskin. (B). Liveliness personnel,executive personnel khususya distribution and (c). Delays in the disbursement of operational funds atdistrict level.Referring to some of the findings in this study, it is necessary to give some suggestions assolutions to problems in this study, as follows: (1) Internal coordination should be increased throughsurveillance team in charge at each level of the implementation team. (2) Lurah need to provide guidanceto apply the principles of the discipline of work for members of the executive team Distribution Raskintold RTS-PMKeywords: Implementation poor rice